The concept of criminology (bathil) in islamic financial institution practices in Malaysia and islamic Republic of Iran / Ezani Yaakub, Noraini Mohamad and Asmak Husin - Yaakub, Ezani; Mohamad, Noraini; Husin, Asmak (Research Management Institute (RMI), 2012)
In Malaysia, Islamic banking system has been established as an alternative to existing conventional systems. The development of Islamic banking in Malaysia is divided into three stages. In the first stage, Bank Islam Malaysia Berhad (BIMB), the only Islamic Bank licensed under the Islamic Banking Act; 1983 was incorporated in March 1983. BIMB, like all banks in Malaysia, whether conventional or Islamic, are supervised by Bank Negara Malaysia (Malaysian Central Bank or BNM). The second stage is the introduction of Skim Perbankan Tanpa Faedah (SPTF) or Interest-free Banking Scheme (IFBS) and Islamic Banking Scheme (IBS). These schemes allowed the existing conventional bank to offer Islamic banking as part of their services. It was launched on 4th March 1993. In the third stage, the government has promoted Malaysia as a regional Islamic Financial Centre. Labuan has been declared as an International Offshore Financial Centre (IOFC). In the year 2002, the first Sovereign Global Islamic Sukuk, structured on the principal of Ijarah, amounting to USD600 million was launched. It signifies Malaysia's strong commitment in developing Islamic Banking and finance in the global front. In fact, Malaysia remains the world's leader in Sukuk issuance by both number and value, with 2010 trade totaling about $40bn and in quarter II on 2011 totaling about $31.5.2 However, the development of prevention method of Islamic financial criminology is insufficient. Most of the prevention was done within conventional framework such as cases of Islamic finance solved and heard in civil court which implements conventional system. In addition to that, most of the wrong-doers are non-Muslim and Muslims who have no exposure to Islamic finance due to their educational background. Thus, this research listed out types of prevention method done by Malaysia and compares the methods to I.R I.R of Iran since I.R of Iran implements full-fledge Islamic finance, and has succeeded to become the leader in Islamic finance among all countries in the world.